Monitoring feral dog’s population at Isla de Cedros, Baja California, and the associated threats over native mastofauna - García-Aguilar, María Concepción (Instituto de Ecología, A.C., 2012)
Monitoring introduced species is an important management tool in order to preserve native species. The aim of this study was to monitor the feral dog’s population in Isla de Cedros and to identify actual and potential threats of their presence over the native mastofauna. Data were collected at two sampling areas of the island, the Northeast Coast (CNE) and the Central-South Region (RCS). Dog’s distribution pattern and density was assess using a non-invasive method based on scat counts along transect surveys and relative density (R) and faecal relative abundance index (fRAI) were estimated. Dog’s diet composition was evaluated by scat analysis. Both R and fRAI were significant greater (P < 0.05) in the CNE than in the RCS. The results showed that feral dogs are feeding from at least three endemic terrestrial mammal species (the mule deer, the brush rabbit, and the Anthony’s pocket mouse) and two pinnipeds species (the northern elephant seal and the California sea lion). With this study provide a useful baseline for future comparison and monitoring and control purposes. Nevertheless, it is necessary to conduct studies about the dog’s feeding behavior to measure their predatory activity and to assess the associated damage level. Also, due to the fact that interactions between dogs and pinnipeds appeared frequently and because they are phylogenetically related, the greatest threat of the dog’s presence is that it could be a disease vector, with serious health outcomes for the wildlife.